Simultaneous separation and purification of chlorogenic acid, epicatechin, hyperoside and phlorizin from thinned young Qinguan apples by successive use of polyethylene and polyamide resins. (1st September 2017) - Sun, Lijun; Liu, Dongjie; Sun, Jiaojiao; Yang, Xingbin; Fu, Minghai; Guo, Yurong
Highlights: The adsorption of the four phenolics on X-5 conformed to Langmuir isotherms better. The adsorption kinetics of CH and EC conformed to pseudo-first-order model better. The adsorption kinetics of HY and PH accorded with pseudo-second-order model better. Qe in preferential adsorption kinetics model was closer to Q0 in Langmuir isotherms. 4 Phenolics were isolated simutaneously by successive use of X-5 and polyamide resins. Abstract: The method for separating and purifying chlorogenic acid (CA), epicatechin (EC), hyperoside (HY) and phlorizin (PH) simutaneously from young Qinguan apples by successive use of X-5 and polyamide resins has been developed in this study. The order of adsorption capacities of X-5 for the four phenolics was PH > HY > EC > CA, and the adsorption equilibriums of the four phenolics onto X-5 resin conformed to Langmuir isotherms preferentially. The adsorption kinetics of EC and CA onto X-5 conformed to the pseudo-first-order model, while that of HY and PH accorded with the pseudo-second-order model. Interestingly, the values of equilibrium adsorption capacities ( Qe ) calculated in the preferential kinetics models were closer to that of theoretical maximum adsorption capacities ( Q0 ) calculated by Langmuir isotherms. Through dynamic adsorption and desorption using X-5 and polyamide resins with ethanol solution as strippant, CA, EC, HY and PH were obtained with purities of 96.21%, 95.34%, 95.36% and 97.36%, respectively.